Faktor-faktor yang berhubungan dengan penerapan triage di instalasi gawat darurat - Widdyastuti, Endah; Hidayah, Nurul; Purborini, Nurul (Borobudur Nursing Review, 2025)
Indonesia as a member of the Association of Southeast Asian Nations (ASEAN), faces a high level of patient visits to the Emergency Room (ER), with the number of patients reaching 4,402,205 in 2017. Triage is a crucial process in handling in the ER that aims to reduce morbidity and mortality. This study aims to identify factors that influence the implementation of triage in the ER of Budi Rahayu Regional Hospital. The method applied is a cross-sectional study with a sample of 10 nurses working in the ER of Budi Rahayu Regional Hospital, Magelang City. The findings of the analysis show that there is no significant relationship between education level and the implementation of triage, because the asymptotic standard error cannot be calculated (zero value), there is no significant relationship between length of service and the implementation of triage with the Chi-Square value obtained is 1.071 and the 2-sided asymptotic significance value is 0.301. However, there was a significant and strong relationship between knowledge and triage implementation, with a lambda value of 1.000 indicating a perfect relationship and strong statistical significance (p = 0.038). In contrast, training did not show a significant relationship with triage implementation, with a two-sided asymptotic significance of 0.778, which is greater than the alpha value of 0.05. In conclusion, knowledge proved to be a significant factor in triage implementation, while education, length of service, and training did not show a significant relationship in this study.